Understanding the role and practice of nursing lecturers in facilitating problem-based learning for nursing students: a Singapore perspective - Mohd Noor, Asmah (2021)
This thesis explores the roles and practice of nursing lecturers facilitating problem-based learning for nursing students in Singapore. Educators have used problem-based learning in teaching nursing students to improve their critical skills in making clinical decisions to improve patients’ outcomes. The study applies the constructivist learning theory as a theoretical framework.